Reused poultry litter microbiome with competitive exclusion potential against Salmonella Heidelberg. Issue 4 (28th May 2020) - Bucher, Maite Ghazaleh; Zwirzitz, Benjamin; Oladeinde, Adelumola; Cook, Kimberly; Plymel, Caroline; Zock, Gregory; Lakin, Steven; Aggrey, Samuel. E.; Ritz, Casey; Looft, Torey; Lipp, Erin; Agga, Getahun E.; et al.
Abstract: The success of poultry litter reuse in U.S. poultry production can be attributed to the efficient treatment methods used by producers during downtimes (the time lapse between consecutive flocks, during which the broiler house is empty). During this period, reused litter may be decaked, tilled/windrowed, or treated with acid‐based amendments to reduce ammonia and bacteria levels. Competitive exclusion, pH, and temperature are proposed factors that influence the level of pathogens and the overall litter microbiome during downtimes. We previously reported on the bacterial genetic factors associated with the fitness of two strains of Salmonella enterica serovar Heidelberg (SH) incubated for 14 d in reused litter. Here, we investigated the physicochemical parameters and the microbiome of the litter correlating with SH abundance during this period. We used 16S ribosomal RNA gene sequencing to determine the litter microbiome and whole genome sequencing to characterize bacteria with competitive exclusion potential against SH. The β diversity of the litter microbiome was significantly affected by the duration of incubation, microcosm, and microcosm plus Heidelberg strain combinations. In addition, β diversity was significantly affected by litter parameters, including NH4, pH, moisture, water activity, and aluminum. The major phyla observed in the reused litter throughout the 14‐d incubation experiment were Firmicutes and Actinobacteria, although their abundance differed by microcosm and time. Amplicon‐specific variants homologous to the members of the genera Nocardiopsis and Lentibacillus and the family Bacillaceae_2 were found to significantly correlate with the abundance of Salmonella . A consortium of Bacillus subtilis strains isolated from the litter microcosms reduced the growth of SH in vitro.